Persepsi Guru Sejarah Tentang Kurikulum Sekolah Penggerak Di SMA Negeri 3 Gorontalo - Dini Aminarti Sugeha; Resmiyati Yunus; Tonny Iskandar Mondong (KOLONI, 2023)
The purpose of this study was to find out how the history teacher's perception of the driving school curriculum at SMA Negeri 3 Gorontalo. by using qualitative methods, the researcher attempted to gather information related to the driving school curriculum that had been implemented in SMA Negeri 3 Gorontalo. In this process the researcher explores whether this curriculum has been successfully implemented or has experienced various obstacles in its implementation so that it has an impact on the student learning process. The results of his research are the implementation of driving schools in SMA Negeri 3 Gorontalo through the activities of school principals who take part in selection in the form of essays. The realization that SMA Negeri 3 became a driving school because it was considered superior in terms of achievement. Driving school is a government program with the aim of separating competence capacity as a teacher, which in substance the implementation of driving schools in SMA 3 Gorontalo City is considered very good because it adds insight in carrying out learning on the implementation of driving schools in SMA 3 Kota has been implemented for in years since 2021.  Keywords: Teacher's Perception, Driving School, Curriculum.